Credit Risk, Capital Adequacy, Liquidity and Profitability of Badung Regency Village Credit Institutions - I Gusti Agung Putu Nadya Aundria Paramita; I Nyoman Wijana Asmara Putra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
The research aims to empirically examine the influence of credit risk, capital adequacy and liquidity on LPD profitability in Badung Regency. In this research, the data used is secondary data from the Badung Regency LPD financial reports, which has a total sample of 94 LPD samples for the period 2020 and 2021. The sample determination method uses the Simple Random Sampling technique. This data was collected using non-participant observation methods. The data analysis technique used is Multiple Linear Regression analysis. The results of the analysis from this research show that Credit Risk has a negative effect on LPD profitability, Capital Adequacy has a positive effect on LPD profitability and Liquidity has no effect on Badung Regency LPD profitability. It is hoped that the implications of this research can contribute to the development of knowledge regarding accounting regarding the influence of credit risk, capital adequacy and liquidity on LPD profitability.